Citizen science in community-based watershed management: an institutional analysis in Ethiopia - Nigussie, Likimyelesh; Haile, Alemseged Tamiru; Gowing, J.; Walker, D.; Parkin, G. (International Water Management Institute, 2020)
The engagement of communities (non-scientists) in the collection of reliable hydrometeorological data (a citizen science approach) has the potential to address part of the data gaps in Ethiopia. Due to the high cost of establishing and maintaining gauging stations, hydrometeorological monitoring in the country tends to focus on large river basins (> 1,000 km2) with little or no consideration of small watersheds (< 100 km2). However, hydrologic data from small watersheds are critical for two main reasons: (i) measure the impacts of watershed management interventions on water resources; and (ii) inform local development plans, such as small- and micro-scale irrigation development. Therefore, this paper examines the institutional arrangements for hydrometeorological monitoring and the practices followed by the Basin Development Authority and National Meteorology Agency in Ethiopia. It is important to investigate the possibilities of embedding a citizen science approach into the data collection systems of these two organizations, as this will help to address data gaps, particularly at micro-watershed levels. Based on the assessments, there is potential to embed the approach into the institutional structure of the Ministry of Agriculture (MoA) for hydrometeorological monitoring in micro-watersheds, due to the following reasons: (i) MoA has a high demand for hydrometeorological data from small rivers to be used for small- and micro-scale irrigation development, and for measuring the impacts of watershed development interventions on water resources; and (ii) MoA has an institutional structure from federal to community level that supports the engagement of communities in development interventions. However, effectively embedding the citizen science approach into regular monitoring of MoA depends on the clear distribution of mandates; developing legal, ethical, methodological and quality frameworks; and developing clear data sharing and incentive mechanisms involving all partners.